Biogeografia neutra e a evolução de redes complexas de interações bióticas - Coelho, Marco Túlio Pacheco (2016)
A contemporary goal in ecology is to determine the ecological and evolutionary processes that generates the recurring structural patterns in mutualistic networks. One of the greatest challenges is testing the capacity of neutral processes to replicate observed patterns in ecological networks, since original formulation of neutral theory lacks trophic interactions. Here, we developed a stochastic simulation neutral model adding trophic interactions to the neutral theory of biodiversity. We show that our model is able to reproduce accurately the evolutionary conservatism of interacting species, as well as the most common structural patterns observed in nature. Moreover, we found that evolutionary conservatism of interacting species increases with lowmigration rate.Low migration rates promote both spatial and temporal autocorrelation of phylogenetic related species, which have a higher chance of interacting randomly with the same set of partners. Random migration , in addition to speciation and probability of interaction, are also partially responsible for connectance, degree distribution, and nested structure of mutualistic networks. These findings have broad implications to the interpretation of niche-based processes as unique drives of ecological networks, as well as the integration of network structures with demographic stochasticity.